The Impact of Clinical Pharmacist Implemented Protocol on Albumin Utilization and Cost in an Intensive Care Unit in Egypt - Dina Mohamed Ibrahim; May Ahmed Shawki; Mohamed Hassan Solayman; Nagwa Ali Sabri (Frontiers in Pharmacology, 2022)
Introduction: Albumin is an expensive non-blood plasma substitutes with limited availability that has been reported to be inappropriately used in healthcare settings. Hence, interventions are recommended to control its misuse.Objective: To evaluate the impact of clinical pharmacist implemented dispensing protocol on optimization of albumin use in an intensive care unit (ICU).Design: A retrospective prospective 3-phase interventional study was conducted in an ICU in a tertiary Egyptian hospital over a period of 2 years.Methods: The study included three phases; a preparation phase where a local albumin dispensing protocol and a restriction dispensing form were prepared by clinical pharmacists and was approved by the local Drugs and Therapeutics Committee, a retrospective pre-implementation phase in which the medical records of all ICU patients receiving albumin were evaluated for appropriateness of albumin use according to the developed protocol, and a prospective implementation phase where the dispensing protocol and restriction dispensing form were applied. The pattern of albumin consumption and cost were recorded and compared between the retrospective and prospective phases.Results: In the retrospective phase, 190 ICU patients received albumin of whom 83.6% was considered inappropriate indications for albumin compared to only 44 patients in the prospective phase of whom 16% was considered inappropriate (p-value <0.001). Clinical pharmacists’ interventions significantly decreased the inappropriate albumin consumption from 4.7 vials/patient in the retrospective phase to 2.7 vials/patient in the prospective phase (p-value <0.001) with a total cost savings of 313,900 Egyptian Pounds (19,930 US Dollars).Conclusion: The current study showed that clinical pharmacists’ interventions led to a significant control on albumin use and consequently reduced the cost associated with its consumption.